Some empirical models of Japanese government bond yields using daily data - Tanweer Akram; Huiqing Li (Levy Economics Institute of Bard College, 2020)
This paper models the dynamics of Japanese government bond (JGB) nominal yields using daily data. Models of government bond yields based on daily data, such as those presented in this paper, can be useful not only to investors and market analysts, but also to central bankers and other policymakers for assessing financial conditions and macroeconomic developments in real time. The paper shows that long-term JGB nominal yields can be modeled using the short-term interest rate on Treasury bills, the equity index, the exchange rate, commodity price index, and other key financial variables.
Keywords: E43; E50; E58; E60; G10; G12; 330; Japanese Government Bonds; JGBs; Long-Term Interest Rates; Nominal BondYields; Monetary Policy; Bank of Japan; John Maynard Keynes